The Freedom of the "Little Prince". Ordinary Tales of Business in the Public Domain - Bozzarelli, Oriana (RiCOGNIZIONI. Rivista di Lingue e Letterature straniere e Culture moderne, 2017)
This paper deals with recognizing the public domain as a fundamental common heritage through a case study analysis. Public domain legal protection will be taken into account, too. In particular, the case study is referred to the universally known work of Antoine de Saint-Exupéry "Le Petit Prince", which in 2015 entered into public domain in all Europe apart France. In this Country, because of a number of measures, the works of Saint-Exupéry will be protected by copyright until 2032. In addition, the The Little Prince characters were registered by the aviator and writer’s heirs as trademarks, which duration is potentially unlimited.